Inpatient plus Post-discharge Durations of Therapy to Identify Antimicrobial Stewardship Opportunities at Transitions of Care. (4th October 2017) - Dyer, April; Ashley, Elizabeth Dodds; Anderson, Deverick J; Sarubbi, Christina; Wrenn, Rebekah; Hicks, Lauri; Srinivasan, Arjun; Moehring, Rebekah W
Abstract: Background: In-hospital antimicrobial durations capture only a portion of total antimicrobial exposures attributable to that inpatient stay. Review of electronic discharge prescriptions could allow stewards to identify excessive prescribing durations. Methods: We performed a retrospective review of inpatient and discharge antimicrobial prescribing at three hospitals from April to September 2016 using two data sources: electronic medication administrations and electronic prescription orders at discharge. Antimicrobial agents from the National Healthcare Safety Network Antimicrobial Use (NHSN AU) module were included. Durations were calculated for admissions in which patients received at least one dose of an antimicrobial agent on inpatient units. Intended post-discharge durations were captured in days duration fields or calculated from sig and quantity fields of discharge prescriptions. Post-discharge days and inpatient days were summed to calculate the total duration of therapy resulting from the admission. Descriptive statistics were used to describe inpatient, post-discharge, and total durations. Results: Among 45, 693 inpatient admissions, NHSN AU antimicrobials were given during 23, 447 inpatient admissions (51%) and in electronic discharge prescriptions for 7, 442 admissions (16%). Median total duration was 4 days (IQR 2–11) among all patients who received antimicrobials and 12 (IQR 9–17) among those who received discharge prescriptions. Common post-discharge durations were 5, 7, and 10 days (Figure 1). Post-discharge days accounted for 40% (78, 195/196, 792) of the total days of antimicrobial therapy. The most common discharge agents were ciprofloxacin (14%), amoxicillin/clavulanate (11%), and levofloxacin (8%). Most discharge prescriptions originated from medical (37.1%), surgical (15.6%), and hematology/oncology wards (14.5%). Conclusion: Post-discharge days accounted for 40% of antimicrobial days related to inpatient admissions. Common post-discharge durations suggested clinicians were not counting inpatient days when completing discharge orders. Post-discharge days were feasibly captured through electronic prescribing records and could aid in targeting stewardship interventions at transitions of care. Disclosures: All authors: No reported disclosures.